The Crucial Role of Educational Stakeholders in the Appropriation of Foreign Language Education Policies: A Case Study (2017)
Drawing on the concept of policy appropriation, this study investigates how different education stakeholders in a rural region of Colombia perceive foreign language education policies, and how these perceptions shape the way they recreate these reforms at the ground level. Contributing to the field of language policy analysis in Colombia and abroad, findings in this study not only provide knowledge on foreign language policymaking processes in rural areas in Colombia, but also shed light on the active role played by different stakeholders in the continuous recreation and appropriation of language education reforms.